Trubarovi imaginarni čitatelji: problem autorske knjižne posvete u protestantskoj literaturi 16. stoljeća - Đurić, Aleksandra (Slavia Centralis, 2020)
Trubar’s imaginary readers: the problem of authorial inscriptions in Protestant literature of the 16th century This article describes interdisciplinary research linking knowledge of literary history, language and history. It analyzes the historical value of two inscriptions (posvete) by Primož Trubar (1508–1586) found in the book Ta prvi dejl tiga noviga testamenta published in 1557 and the book Glagolski prvi del novoga testamenta published in 1562. The author believes that these "posvetila" are key to exploring the relationships and attitudes of people in the Early Modern Age. The task is to imaginatively envision Trubar’s readers and show the interplay of spiritual and cultural diversity in the Pannonian region in the Early Modern Age.